How to seal your own fate - Perrin, Kristen (New York : Dutton, 2025)
"Welcome to Castle Knoll, the idyllic English village home to a surprising number of murderers. Present day: Annie Adams is just settling into life in Castle Knoll when local fortune teller Peony Lane shares a cryptic message only hours before being found dead inside the locked Gravesdown Estate. Annie has no choice but to delve into the dark secrets of her new countryside home in order to find out just what Peony Lane was trying to warn her about, before her brand new life comes crashing down around her. 1967: Teenage Frances Adams, Annie$1 (Bs great aunt, finds herself caught between two men. Ford Gravesdown is one of the only remaining members of a family known for its wealth and dubious uses of power. Archie Foyle is a local who can$1 (Bt hold down a job and lives above the village pub. But when Frances teams up with Archie to investigate the car crash that killed most of Ford's family, it quickly becomes clear that this was no accident$1 (Bhints of cover-ups, lies, and betrayals abound." -- Book jacket.s
Keywords: Murder -- Investigation -- Fiction; Women detectives -- Fiction; Secrecy -- Fiction; Fortune-telling -- Fiction; Inheritance and succession -- Fiction; Villages -- England -- Fiction; England -- Fiction; Detective and mystery fiction